Assessment of Teachers’ Knowledge toward Communicable Diseases in Primary School - Abbas Ahmed, Fadhil; Jassim Mohammed, Hussein (International Journal of Psychosocial Rehabilitation, 2020)
Methods: A descriptive study design was conducted on primary school teachers, starting from December 2019 to March 2020, in order to identify the scope of primary school teachers’ knowledge concerning communicable diseases. A non-probability (purposive) sample of 250 teachers was selected from 50 primary schools in the Alhawija district in Kirkuk Governorate. The data were collected by the investigator, who interviewed teachers in their primary schools and filled out the constructed questionnaire formats, which were designed for the purpose of the study.Results: The findings revealed that the level of teachers’ knowledge was low about communicable diseases in general, which was considered not enough to prevent the spread of communicable diseases in primary schools.Conclusion: This shows that the primary school teachers have poor knowledge related to communicable diseases.